Α-Linolenic acid and linoleic acid modulate the lipidome and the skin barrier of a tissue-engineered skin model. (1st March 2022) - Simard, Mélissa; Tremblay, Andréa; Morin, Sophie; Martin, Cyril; Julien, Pierre; Fradette, Julie; Flamand, Nicolas; Pouliot, Roxane
Abstract: Polyunsaturated fatty acids (PUFAs) play an important role in the establishment and the maintenance of the skin barrier function. However, the impact of their derived lipid mediators remains unclear. Skin substitutes were engineered according to the self-assembly method with a culture medium supplemented with 10 μM of both α-linolenic acid (ALA) and linoleic acid (LA). The supplementation with ALA and LA decreased testosterone absorption through a tissue-engineered reconstructed skin model, thus indicating an improved skin barrier function following supplementation. The exogenously provided fatty acids were incorporated into the phospholipid and triglyceride fractions of the skin substitutes. Indeed, the dual supplementation increased the levels of eicosapentaenoic acid (EPA) (15-fold), docosapentaenoic acid (DPA) (3-fold), and LA (1.5-fold) in the epidermal phospholipids while it increased the levels of ALA (>20-fold), DPA (3-fold) and LA (1.5-fold) in the epidermal triglycerides. The bioactive lipid mediator profile of the skin substitutes, including prostaglandins, hydroxy-fatty acids, N -acylethanolamines and monoacylglycerols, was next analyzed using liquid chromatography-tandem mass spectrometry. The lipid supplementation further modulated bioactive lipid mediator levels of the reconstructed skin substitutes, leading to a lipid mediator profile more representative of the one found in normal human skin. These findings show that an optimized supply of PUFAs via culture media is essential for the establishment of improved barrier function in vitro . Statement of significance: Supplementation of the culture medium with 10 μM of both α-linolenic acid (ALA) and linoleic acid (LA) improved the skin barrier function of a tissue-engineered skin model. The exogenously provided fatty acids were incorporated into the phospholipid and triglyceride fractions of the skin substitutes and further modulated bioactive lipid mediator levels, including prostaglandins, hydroxy-fatty acids, N -acylethanolamines and monoacylglycerols. These findings highlight the important role of ALA and LA in skin homeostasis and show that an optimized supply of polyunsaturated fatty acids via culture media is essential for the establishment of improved barrier function in vitro . Graphical abstract: Image, graphical abstract